Effect of entomopathogenic fungi on the cattle tick Boophilus microplus (Acari: Ixodida): use of pathogenicity activators - RAYMOND-C., KARIM; ROJAS-B., FABIOLA; BENAVIDES-O., EFRAÍN; COTES, ALBA MARINA; VILLAMIZAR, LAURA; RONDEROS-J., VANIA; GARCÍA-M., PAOLA (Revista Colombiana de Entomología, 2004)
In arthropod-pathogen systems, the value of using pathogenicity activators to improve growth, sporulation capacity and adherence of entomopathogenic fungi to arthropods has been demonstrated. The objective of the work was to study the biocontrol activity of two isolates of Metarhizium anisopliae (Mt019 and Mt020) on the tick Boophilus microplus, by examining the use of pathogenicity activators used during the fungal culture phase. A completely randomized design was used. testing three treatments applied by aspersion: culture on traditional agar (EM), media plus unspecific pathogenicity activator (S) and the same media with a tick-specific activator (SA). The experimental unit was a group of ten engorged ticks (five replicates) and fungal concentration was constant at 108 conidia ml-1. Analysis of the results was based on the parameters IEC (Conversion Efficiency lndex) and ER (Reproductive Efficacy), indicators of reproductive capacity of the tick and PCIEC (Percentage Control of IEC), and PCONER (Percentage Control ER), associated with fungal efficacy. There was an effect of pathogenicity activators on the two fungi evaluated; the IEC value was lower (p< 0,01) in groups with activator. In the case of ER. values were lower for groups with activator but not statistically significant. Control levels (PCIEC and PCONER) were significantly higher (p< O.O 1) in the two treatments with activator for both parameters in the two fungal isolates. It was concluded that the use of pathogenicity activators during the culture phase is a process that ensures a better biocontrol effect of fungi on ticks.